Adalimumab effect on pain in hidradenitis suppurativa patients: systematic review and meta-analysis - Aikaterini Tsentemeidou; Elena Sotiriou; Nikolaos Sideris; Alexandra Kourouklidou; Aimilios Lallas; Dimitrios Ioannides; Efstratios Vakirlis (Mattioli1885, 2022)
Introduction: Pain is experienced by most patients with hidradenitis suppurativa (HS) and has a severe impact on their quality of life. Its management still presents a challenge. Adalimumab, a TNF-a antagonist, has shown promising results in HS-related pain reduction. Objectives: To aggregate and synthesize all existing evidence regarding the effect of adalimumab on HS-associated skin pain. Methods: We identified original controlled and uncontrolled studies with participants receiving adalimumab, which included change in pain score post-treatment comparing to baseline as an endpoint. We searched MEDLINE, ScienceDirect, the Cochrane Library, ClinicalTrials.gov and International Clinical Trials Registry Platform. The primary endpoint of our study was mean change (continuous variable) of pain scores at week 12 comparing to baseline. Results: We performed a meta-analysis of four randomized controlled trials (282 patients in the intervention group and 266 patients in the control group). Adalimumab brought about a 0.418 reduction in mean pain score at its worst with 95%CI [-0.588, -0.248] and p = 0.000 at 12 weeks after treatment commencement. Four more studies were included in a qualitative synthesis, two of which reported statistically significant reduction in pain scores at week 12. Conclusions: Adalimumab could be prescribed more readily in cases of hidradenitis associated with significant skin pain.